The Power of Dai- Dai Virtual: Peran Dakwah dalam Literasi Pesan terkait Covid 19 di Era Post Truth - Khadijah Arnus, Sri; Prio Utomo, Agus; Mamis, Subriah (Meyarsa: Jurnal Ilmu Komunikasi dan Dakwah, 2022)
Facts and news hoaxes about Covid-19 are widely scattered in the media. This creates panic and confusion in the audience. In the midst of public confusion about the confusion of information, on the other hand the figure of a preacher or "virtual opinion leader" often provides views on topics circulating in society and social media from an Islamic point of view, through the da'wah they convey. This study aims to examine the role of virtual dai-dai in providing literacy to the public regarding Covid 19 messages on social media. This type of research is descriptive qualitative. Data collection was done by interview method. This research was conducted in Baruga District, Kendari City. The criteria for informants are in the age range of 17-30 years, social media users, and often access religious lectures from social media such as YouTube, Instagram and Facebook. Based on the results of the study, the virtual dai-dai who gave the most literacy to messages related to Covid 19 were Ustadz Das'at Latief, Ustadz Somad and Aa Gym. Ustadz Das'at Latif relatively often appears to give explanations regarding Covid 19, both in mainstream media and in virtual media, even the Ministry of Health uses him in public service advertisements for Covid 19. The style of language that is interspersed with humor, uses a typical Sulawesi speaking style to make the audience more easily understands the explanations of the preachers in reviewing the Covid 19 problem from the point of view of the Qur'an and Hadith. In the midst of a crisis of public trust regarding information circulating in the community, there is another power that can provide this understanding, namely the power of virtual dai-dai.